Synchronization and anchoring of two non-harmonic canonical-dissipative oscillators via Smorodinsky-Winternitz potentials - Mongkolsakulvong, S.; Frank, T.D. (Condensed Matter Physics, 2017)
Two non-harmonic canonical-dissipative limit cycle oscillators are considered that oscillate in one-dimensional
Smorodinsky-Winternitz potentials. It is shown that the standard approach of the canonical-dissipative framework to introduce dissipative forces leads naturally to a coupling force between the oscillators that establishes
synchronization. The non-harmonic character of the limit cycles in the context of anchoring, the phase difference between the synchronized oscillators, and the degree of synchronization are studied in detail. Розглянуто канонiчно-дисипативнi граничнi цикли для двох негармонiчних осциляторiв, що коливаються в одномiрних потенцiалах Смородинського-Вiнтернiца. Показано, що стандартний канонiчнодисипативний пiдхiд iз введенням дисипативних сил природно приводить до появи взаємодiї мiж осциляторами, яка синхронiзує їх рух. Детально дослiджено негармонiчний характер граничних циклiв у контекстi анкерування, рiзницю фаз мiж синхронiзованими осциляторами та ступiнь їх синхронiзацiї.